(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
This report from the field describes some of the author’s methods of audience engagement as a means of social engagement, discussing the implications for practice. The report invites dialogue with the reader about the usefulness of audience engagement and ways it can be manifested before, during and after performance. Theatre is a vibrant and valuable tool for sparking dialogue and inspiring action around challenging social topics. Audiences who are engaged in the process of the performance beyond the standard role of passive spectator are more likely to be motivated to deliverable endeavors post performance. This report from the field offers four brief case studies as examples of audience engagement and includes pragmatic techniques for using theatre as a vehicle for personal and social change through audience engagement. It explores how artists can galvanize and empower audiences by creating experiential communities pre, during, and post-show. Drawing upon examples from high-quality international theatre projects written and directed by the author, the essay investigates and describes the work of The H.E.A.T. Collective including My Heart is in the East (U.S., U.K. and Europe), The FEAR Project (produced in the US, India and Czech Republic), Emma Goldman Day (U.S.).